Post-surgical outcomes in transgender women: a prospective analysis of sexual function and health-related quality of life - Wenk, Maren; Rademacher, Natalie; Liedl, Bernhard; Grüne, Britta; Meister, Benjamin (World journal of urology, 2025)
To prospectively evaluate patient and clinician reported outcomes of sexual function and health-related quality of life (QOL) of transgender women preoperatively (t0), 6 months (t1), and 12 months (t2) after gender-affirming surgery (GAS) with penile inversion vaginoplasty.
Gesehen am 30.10.2025